Inovasi Manajemen Peserta Didik : Strategi Peningkatan Efektivitas Pembelajaran di SMP Muhammadiyah 2 Taman - Junivan; Akmalia Ramadhani, Najwa; Aula Rahma Putri; Muhammad Latif Fatkurrohman; Ayu Wulandari (CV Putra Publisher, 2024)
This study aims to analyze the Innovation of Student Management Strategies on the Effectiveness of Learning for Students of SMP Muhammadiyah 2 Taman with a focus on three main elements: Planning, Implementation, and Evaluation. The method used is a Qualitative study, namely an interview with the Deputy Head of Curriculum of SMP Muhammadiyah 2 Taman regarding the three main elements of the research focus. which then the data will be reduced and made relevant to the results of previous research through journals and books to create further understanding. The results obtained indicate that SMP Muhammadiyah 2 Taman has implemented an innovative learning system, namely developing discipline by accustoming students to be active in class and limiting the use of cellphones at school, and spiritual experience, namely obeying Islamic religious knowledge through reciting the Koran according to their abilities, with levels of tajwid, tilawah, the Koran, and memorization. And there is an istighfar treatment for students who violate the rules inside and outside of learning, they are asked to reflect on the mistakes they have made. Because this school is an Islamic school, teachers are required to help students understand the teachings of the Koran and Hadith. This innovation is given to prepare students for the future.